Clinical implications of U2AF1 mutation in patients with myelodysplastic syndrome and its stability during disease progression. Issue 11 (3rd September 2013) - Wu, Shang-Ju; Tang, Jih-Luh; Lin, Chien-Ting; Kuo, Yuan-Yeh; Li, Li-Yu; Tseng, Mei-Hsuan; Huang, Chi-Fei; Lai, Yen-Jun; Lee, Fen-Yu; Liu, Ming-Chih; Liu, Chia-Wen; Hou, Hsin-An; et al.
<x xml:space="preserve">Abstract</x> We aimed to analyze clinical impacts of the U2AF1 mutation on patients with myelodysplastic syndrome (MDS) and its stability during disease progression. We checked mutation status of the U2AF1 by direct sequencing in 478 de novo MDS patients and correlated with the clinical characteristics and outcomes. We also sequentially analyzed the U2AF1 mutation in 421 samples from 142 patients to determine its stability during the disease courses. Thirty‐six patients (7.5%) were found to have U2AF1 mutations, which occurred more frequently in younger patients (P = 0.033). U2AF1 mutation was an independent poor‐risk factor for overall survival (OS) in all patients (P = 0.030) and younger patients (P = 0.041). U2AF1 mutation could also predict shorter time‐to‐leukemia transformation (TTL) in younger patients (P = 0.020). In addition, U2AF1 mutation was associated with shorter TTL in lower‐risk MDS patients. Sequential analyses showed all original U2AF1 mutations in U2AF1‐mutated patients were retained during follow‐ups unless complete remission was achieved, whereas none of the U2AF1‐wild patients acquired a novel mutation during disease evolution. U2AF1 mutation is more prevalent in younger MDS patients and associated with inferior outcomes although it is stable during the clinical course. The mutation may be used as a biomarker for risk stratification. Am. J. Heamtol. 88:E277–E282, 2013. © 2013 Wiley Periodicals, Inc.